UNICEF : global governance that works - Jolly, Richard (London : Routledge, 2014)
'UNICEF is one of the best known organizations of the United Nations system and the oldest of the UN's development funds. It is also the part of the UN which consistently receives support from all countries round the world, including the United States. This book brings out the wider reasons for UNICEF's success and popularity, setting them in the context of UNICEF's evolution since 1946 and drawing lessons for other international organizations. This will be of great interest to all scholars of international organisations, development, human rights and the United Nations system'--
1. The vision of two early giants, 1946-60 -- 2. Planning for children and the role of economists, 1960-70 -- 3.'Basic services' and'health for all,' 1970-80 -- 4. The Jim Grant years, 1980-95 -- 5. Nutrition, WASH, education, and children in especially difficult circumstances -- 6. The human rights-based approach, 1995-2010 -- 7. UNICEF today -- 8. Conclusions for global governance and the UN.
Includes bibliographical references and index.
Mode of access : World Wide Web.
Keywords: UNICEF -- History; Child welfare -- Developing countries -- History